Young Employee Security During the COVID-19 Pandemic—Polish Case Study - Edyta Bombiak (Librelloph, 2021)
Security issues and human lives have always been inseparable. The feeling of security is the basic need of every individual. The outbreak of the pandemic has had major consequences for the operation of enterprises and their employees. The latter have faced a new, unpredictable, and rapidly changing situation, which has increased the level of fear and decreased the perception of security. The purpose of the research was to evaluate the impact of the Covid-19 pandemic on the perception of security of young Polish employees. To rate the level of security, the 5-degree Likert Scale was used. Furthermore, an attempt was made to determine whether actions undertaken by employers with respect to employee security improvement have been sufficient, or if it is necessary to expand the scope of support. In the course of analyses, it was established that the pandemic reduced the level of working conditions and economic security and had a negative impact on the physical and mental wellbeing of young employees.